Association of HPV35 with cervical carcinogenesis among women of African ancestry: Evidence of viral‐host interaction with implications for disease intervention. Issue 10 (16th May 2020) - Pinheiro, Maisa; Gage, Julia C.; Clifford, Gary M.; Demarco, Maria; Cheung, Li C.; Chen, Zigui; Yeager, Meredith; Cullen, Michael; Boland, Joseph F.; Chen, Xiaojian; Raine‐Bennett, Tina; Steinberg, Mia; et al.
Abstract: HPV35 has been found in only ∼2% of invasive cervical cancers (ICC) worldwide but up to 10% in Sub‐Saharan Africa, warranting further investigation and consideration of impact on preventive strategies. We studied HPV35 and ethnicity, in relation to the known steps in cervical carcinogenesis, using multiple large epidemiologic studies in the U.S. and internationally. Combining five U.S. studies, we measured HPV35 positivity and, in Northern California, observed HPV35 type‐specific population prevalence and estimated 5‐year risk of developing precancer when HPV35‐positive. HPV35 genetic variation was examined for differences in carcinogenicity in 1053 HPV35+ cervical specimens from a U.S. cohort and an international collection. African‐American women had more HPV35 (12.1% vs 5.1%, P  < .001) and more HPV35‐associated precancers (7.4% vs 2.1%, P  < .001) compared to other ethnicities. Precancer risks after HPV35 infection did not vary by ethnicity (global P = .52). The HPV35 A2 sublineage showed an increased association with precancer/cancer in African‐Americans (OR = 5.6 vs A1, 95% CI = 1.3‐24.8) and A2 was more prevalent among ICC in Africa than other world regions (41.9% vs 10.4%, P  < .01). Our analyses support a strong link between HPV35 and cervical carcinogenesis in women of African ancestry. Current HPV vaccines cover the majority of cervical precancer/cancer across all ethnic groups; additional analyses are required to determine whether the addition of HPV35 to the already highly effective nine‐valent HPV vaccine would provide better protection for women in Africa or of African ancestry. Abstract : What's new? HPV35 accounts for 2% of invasive cervical cancers worldwide, but possibly as much as 10% in sub‐Saharan Africa. These authors found that African‐American women had higher rates of HPV35 infection, and more precancers associated with HPV35, than women of other ethnicities. However, precancer risk by HPV35 status did not vary by ethnicity. Genetic testing uncovered an association between precancer and the A2 sublineage of HPV35 within Africa and among African‐American women in the US. Additionally, particular HPV35 SNPs, including one in the E7 oncogene, were associated with precancer or cancer. Recognizing the importance of HPV35 in women of African ancestry could help improve HPV screening tests or vaccines.